2005
DOI: 10.1111/j.1468-2370.2005.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Using knowledge within small and medium‐sized firms: A systematic review of the evidence

Abstract: This paper provides a systematic review of the literature on how small and medium-sized enterprises (SMEs) use and acquire knowledge. The review was undertaken as part of the Economic and Social Research Council's Evolution of Business Knowledge Programme. The paper describes the systematic review protocol and provides a detailed explanation of the methods used. From the review, it is evident that SME knowledge research concentrates primarily on the acquisition and use of knowledge, treating it as an asset tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
525
0
26

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 630 publications
(563 citation statements)
references
References 126 publications
(302 reference statements)
12
525
0
26
Order By: Relevance
“…It has been amply acknowledged that it is hugely important for SMEs to have access to knowledge produced by others, which often demands an interaction between the parties (Egbu et al, 2005;Thorpe et al, 2005;Chen et al, 2006;Desouza & Awazu, 2006;Durst & Edvardsson, 2012). But our understanding on the matter of knowledge management and relationships in SMEs is not enough to give us a whole, detailed picture of this connection, and to clearly bring out the differences between SMEs and larger-scale enterprises.…”
Section: Studies On Knowledge Management In Smesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been amply acknowledged that it is hugely important for SMEs to have access to knowledge produced by others, which often demands an interaction between the parties (Egbu et al, 2005;Thorpe et al, 2005;Chen et al, 2006;Desouza & Awazu, 2006;Durst & Edvardsson, 2012). But our understanding on the matter of knowledge management and relationships in SMEs is not enough to give us a whole, detailed picture of this connection, and to clearly bring out the differences between SMEs and larger-scale enterprises.…”
Section: Studies On Knowledge Management In Smesmentioning
confidence: 99%
“…This is the impression that we get from the literature reviews conducted on knowledge management in SMEs. Thorpe et al (2005) provide a systematic review of the literature on how SMEs use knowledge, selecting 69 articles published up until 2004. Some of these articles correlate the use of knowledge with its acquisition by means of relationships with parties outside the enterprise.…”
Section: Studies On Knowledge Management In Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, know how can be easily transferred among firm's staff in informal way. However, acquiring, generating and sharing knowledge with others (outside of the firm) are viewed as primary processes in organizational evolution (Thorpe et al 2005). Learning from others' experience through a process of knowledge transfer is a key way to foster a firm's competitive advantage (Hutzschenreuter and Horstkotte 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we provide a review of peer-reviewed articles published in leading journals from 2000 to 2017. The systematic literature review methodology presented in this paper is based on the seminal works of Tranfield et al (2003), Thorpe et al (2005), Matthews and Marzec (2012). The review process consists of four stages and the flow is shown in …”
Section: Methodsmentioning
confidence: 99%